Pengembangan LKPD Berbasis Discovery Learning Dengan Pendekatan Teaching at The Right Level Pada Materi Ikatan Kimia SMA/MA - Sudirman; Charine Vivinia Lado; Daud Dakabesi (LPPM Universitas Negeri Jakarta, 2026)
This study aims to determine the form of the developed product, the level of validity, and student responses to the Discovery Learning-based worksheets using the TaRL approach on the chemistry bonding material for 11th-grade MIPA students in the 2025/2026 academic year. Although previous studies have integrated TaRL and Discovery Learning as separate approaches, no research has produced a differentiated worksheet specifically targeting chemical bonding concepts for high school students. The method used research and development (R&D) using the ADDIE development model. The developed worksheets were validated by subject matter experts and media experts and tested on students through small-group and large-group trials at State Senior High School 3 Kupang in Grade 11. The research data using a Likert scale to determine the product’s validity level. The research produced a worksheet featuring chemical bonding material presented through text and images. The worksheet is organized according to the Discovery Learning syntax and incorporates the Teaching at the Right Level approach. It is differentiated into three levels of student ability (low, medium, and high) to address different educational needs in chemical bonding concepts. The developed worksheets have a high level of validity, with an average validation percentage of 94.67% from subject matter experts, 87.88% from media experts, 98.52% from students in the small-group pilot test and 99.33% in the large-group pilot test. Based on the research results, the developed worksheets are suitable for use as teaching materials to support students’ understanding according to their cognitive ability levels. The scope of this study is confined to the development, validation, and student response stages. Future research should include effectiveness testing to assess improvements in learning outcomes.